2020
DOI: 10.1007/s11325-020-02037-w
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea syndrome (OSAS) and swallowing function—a systematic review

Abstract: Objectives The purpose of this systematic review was to summarize and qualitatively analyze published evidence elucidating the prevalence of dysphagia and detail alterations in swallowing function in patients with OSAS. Methods Computerized literature searches were performed from four search engines. The studies were selected based on the inclusion and exclusion criteria. The studies were screened using Covidence (Cochrane tool) and followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 46 publications
1
19
0
2
Order By: Relevance
“…There were no significant differences in temporal parameters among the groups except PTT with 10 ml that OSAS patients have impaired swallowing, such as premature bolus loss, residue in the hypopharynx, and laryngeal penetration 13,14,23,24 . The most frequently reported abnormality was premature spillage of food 9,10 .…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…There were no significant differences in temporal parameters among the groups except PTT with 10 ml that OSAS patients have impaired swallowing, such as premature bolus loss, residue in the hypopharynx, and laryngeal penetration 13,14,23,24 . The most frequently reported abnormality was premature spillage of food 9,10 .…”
Section: Resultsmentioning
confidence: 79%
“…Similarly, another study of FEES in OSAS patients demonstrated that 27.3% of patients had dysphagia 25 . However, despite the presence of objective swallowing abnormalities, OSAS patients did not voluntarily report symptoms of dysphagia 23,26 . In a recent study, 15% of OSAS patients reported symptoms of dysphagia 12 .…”
Section: Resultsmentioning
confidence: 91%
“…OSAHS is a common breathing disorder, and its mechanisms in modulating this disease were still unclear [17]. Over the past decades, a large number of studies have shown that abnormal DNA methylation epigenetically silences genes necessary for the pathogenesis of human diseases.…”
Section: Discussionmentioning
confidence: 99%
“…One condition associated with dysphagia is obstructive sleep apnea (OSA) [27][28][29] , with increased nocturnal aspiration 30 and risk of aspiration pneumonia 31 . Based on the mechanism proposed by us for viral spread to the lungs, individuals with OSA would thus be expected to be at a higher risk for COVID-19.…”
Section: /8mentioning
confidence: 99%